M-HEALTH FOR ELDERLY - Zulailee, Nuramira Shafinaz (IRC, 2019)
Aging is the process of growing older at cellular, organ, or whole body level throughout the life spam. Thus, as people globally live longer, increasing levels of chronic illness, as well as diminished wellbeing, are nominated to become major global health challenges. Nowadays, there are several apps developed for health care purpose. For example, fitness, diet program, and others. But these mobile apps are designed for the general user and not focused on elderly people. M-health for elderly is a mobile application that is designed for elderly comprises of nutrition and dietary program, suitable fitness and information regarding the disease for elderly. These function are designed for the elderly needs to ease them to use in taking care of their health care since we know mobile apps and device are human assistive in daily life. By using a modern approach of technology, mobile apps are one of the alternatives to provide the proper guidelines in taking a good care of their health care. Thus, it is pertinent to established comprehensive elderly-friendly health care with further focus on preventive action to maintain a healthy life. As a result, m-Health for the Elderly mobile application was developed. To ensure that m-Health for Elderly mobile application are ready to be deployed, the mobile application went through and passes the functionality and acceptance testing.